Indonesia - febriana, sugifebriana_16; Febriana, Sugi; Ariani, Tri (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2025)
This article aims to examine the development of practical instructions based on Contextual Teaching and Learning (CTL) as an effort to improve students' learning outcomes and communication skills through a literature review approach. The writing of this article was motivated by the need for a learning model that not only focuses on cognitive aspects, but also strengthens communication skills and understanding concepts through learning experiences that are relevant to life contexts. The method used is a literature review by examining various appropriate research results, including articles in national journals indexed by SINTA (S1–S5) which discuss the application of CTL in practicum activities. Data were analyzed using a descriptive-comparative approach to reveal patterns, effectiveness, and supporting factors and challenges in implementing CTL in practicum-based learning. The results of the study show that CTL-based practicum guides consistently provide a positive impact on improving learning outcomes through active student involvement and direct learning experiences, as well as helping develop scientific communication skills. It is hoped that this article will become a reference source for educators and researchers in designing learning strategies that are contextual, collaborative, and in line with the competency needs of the 21st century.